Criminality and legitimization in seawaters: a study on the pirates of Malabar during the age of european commercial expansion (1500-1800) - Malekandathil, Pius (2012)
The maritime piracy included a wide variety of associated criminal activities including attack and confiscation of vessels and merchandise, imprisonment or torturing of merchants and rulers in sea-space in return for ransom money, attack and raiding of coastal trading centers and villages, creation of fear and terror in chief channels of navigation and attacking commercial competitors as a strategy to weaken the trading ability and the wealth-mobilizing ability of their rivals. All this applied to coastal south west India during the period under study. The merchant chiefs of Cannanore like Mamale Marakkar and later under Poca Amame (Pokar Ahamad) and Pocarallee (Pokar Ali) were some of the better known protagonists that the Portuguese had to deal with. But the Malabar corsairs had their corresponding English and Sicilian corsairs in the Mediterranean.